2000
DOI: 10.1128/aem.66.9.3960-3965.2000
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Protein Disulfide Isomerase DsbC Stabilizes Multiple-Disulfide-Bonded Recombinant Protein Produced and Transported to the Periplasm in Escherichia coli

Abstract: Dsb proteins (DsbA, DsbB, DsbC, and DsbD) catalyze formation and isomerization of protein disulfide bonds in the periplasm of Escherichia coli. By using a set of Dsb coexpression plasmids constructed recently, we analyzed the effects of Dsb overexpression on production of horseradish peroxidase (HRP) isozyme C that contains complex disulfide bonds and tends to aggregate when produced in E. coli. When transported to the periplasm, HRP was unstable but was markedly stabilized upon simultaneous overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…DsbD should be able to distinguish between the active-site disulfide bonds of substrates such as DsbC and DsbG and other disulfides within the periplasm. By contrast, the substrate-binding interactions of DsbC are sufficiently nonspecific to allow the successful periplasmic expression of recombinant nonbacterial proteins containing multiple disulfide bonds (40)(41)(42)(43)(44). We are interested in learning how DsbC participates in these very different types of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…DsbD should be able to distinguish between the active-site disulfide bonds of substrates such as DsbC and DsbG and other disulfides within the periplasm. By contrast, the substrate-binding interactions of DsbC are sufficiently nonspecific to allow the successful periplasmic expression of recombinant nonbacterial proteins containing multiple disulfide bonds (40)(41)(42)(43)(44). We are interested in learning how DsbC participates in these very different types of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) In addition to PDI, overexpression of Dsb proteins has been shown to increase the yield of various eukaryotic proteins in bacteria. [8][9][10][11][12] Soluble BDNF production was estimated from the biological activity for neurite outgrowth of embryonic chick DRG neurons. Soluble BDNF fractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9) Horseradish peroxidase (HRP) was used as a recombinant protein to investigate the eŠects of coexpressing HRP with molecular chaperons and Dsb proteins. The total HRP production was increased several-fold by overexpression of DsbC 10) and the active HRP production was increased signiˆcantly by coexpression of DsbAB or DsbCD. 11) Human nerve growth factor (NGF) belongs to a neurotrophic factor family.…”
mentioning
confidence: 94%
“…PDI, in addition to inhibiting protein aggregation, may accelerate posttranslational processing of proteins necessary to facilitate insulin uptake [26] . Furthermore, PDI may have a beneficial effect on the secretion of insulin, since overexpression of PDI stabilizes secretory proteins [27] . Misfolded proteins are translocated from the endoplasmatic reticulum, polyubiquinated and transported to cytosolic proteasomes for degradation [23] , but we found that proteasome subunits a and b are down-regulated.…”
Section: Discussionmentioning
confidence: 99%